A transdisciplinary approach to local waste management in New Zealand: Addressing interrelated challenges through indigenous partnership. (October 2015) - Goven, Joanna; Langer, E.R. (Lisa); Baker, Virginia; Ataria, James; Leckie, Alan
Highlights: A transdisciplinary research case study is presented and evaluated. It is successful in meeting four interrelated internal challenges. A partnership with the indigenous community was key to success. Other success factors are identified. Active cultivation of reflexivity promoted integration. De-centring scientific discourse can promote reflexivity. Abstract: The goals of transdisciplinary research (TR) generate several interrelated challenges that are largely internal to the TR process: project ownership, participation, integration, and reflexivity. We examine this set of interrelated challenges, as well as some ways of meeting those challenges, through the lens of a particular case of TR: the Kaikōura Biowaste Project (KBP). We find that the KBP was at least partly successful in meeting each of the four interrelated challenges. Key to that success was our partnership with the local Māori (indigenous) community. External challenges of institutional barriers and political implementation complicated the task of meeting some internal challenges; the KBP had some but not complete success in overcoming these. We find that some familiar factors—co-leadership with an appropriate community partner, early involvement of stakeholders, significant time spent by members of the research team in the case-study community, and sensitivity to communication styles—did indeed contribute to the success of TR. In addition: strong leadership and bridging skills in the research team are key resources for overcoming institutional barriers to integration; pragmatic integration can be accomplished without epistemological interpenetration; and the active cultivation of reflexivity among researchers promotes integration. Reflexivity was facilitated by locating the process in a setting shaped and governed by a worldview different from the dominant scientific discourse, suggesting that, rather than on neutral ground, interactions with less dominant communities should take place in settings and through processes that are familiar to the community but relatively unfamiliar and therefore more challenging to the researchers.